Designing Interactive Multimedia Role Playing Game with Discovery Learning Method for Vocational High School Students - Shalih, Puji Rahmah; Rahman, Eka Fitrajaya; Fitriasari, Novi Sofia (Universitas Pendidikan Indonesia (UPI), 2023)
This research aims to produce learning multimedia based on role playing game with Discovery Learning method in Multimedia Design subject. The making of this multimedia is motivated by the difficulty of improving learning outcomes in Multimedia Design subjects and the need for media assistance to help improve learning outcomes in these subjects. Based on this, a way of learning and media that can help students in learning Multimedia Design subjects are needed, one method that can be used is called the Discovery Learning method. Discovery Learning is a method where learning theory is defined as a learning process that occurs when the learner is not presented with the lesson in its final form, but is expected to organize it himself. This research used the Research and Development (RD) method. The results of this study are: 1) the multimedia built is declared feasible to use with a percentage of 84.32% media experts and 82.00% material experts, 2) student assessment of multimedia gets a percentage of 86.95%, 3) this multimedia can improve the learning outcomes, there’s an increase from the average from 45.8 to 67.3.